PENGARUH METODE PEMBELAJARAN PROBLEM BASED LEARNING DAN PROBLEM SOLVING TERHADAP HASIL BELAJAR SISWA - Suparmi; Febliansyah , Rizky (P3M STKIP 'Aisyiyah Riau, 2023)
This study aims to determine, disclose and describe the Problem Based Learning and Problem Solving Learning Methods on Student Learning Outcomes. The research method that will be used is experiment with a quasi-experiment method. Data processing using a computer program SPSS series 25. Quantitative analysis through t-test, namely hypothesis testing, namely t-test Paired Samples t-Test. the results of research that has been done that the use of Problem Based Learning and Problem Solving methods have an influence on student learning outcomes. From the comparison data of student learning outcomes before and after the use of Problem Based Learning and Problem Solving methods, both the results of the interval scores that have increased, and the average score on the Posttest has increased. Furthermore, based on the results of the t-test calculation, it shows a significant number of 0.001